Environmental impact of invertebrates for biological control of arthropods : (CABI Publishing, 2006)
This book provides an invaluable review of the current methodologies used for assessing the environmental impacts of invertebrate biological agents used to control pests in agriculture and forestry. It explores methods to evaluate post-release effects and the environmental impact of dispersal displacement and establishment of invertebrate biological control agents. It covers methodology on screening for contaminants, the use of molecular methods for species identification and the determination of interbreeding. The book also discusses the use and application of information on zoogeographical zones, statistical methods and risk-benefit analysis